Acid-sensing ion channel blocker diminazene facilitates proton-induced excitation of afferent nerves in a similar manner that Na+/H+ exchanger blockers do - Tkachenko, Yurii; Khmyz, Volodymyr; Buta, Andrii; Isaev, Dmytro; Maximyuk, Oleksandr; Krishtal, Oleg (Frontiers in Cellular Neuroscience, 2023)
Tissue acidification causes sustained activation of primary nociceptors, which causes pain. In mammals, acid-sensing ion channels (ASICs) are the primary acid sensors; however, Na + /H + exchangers (NHEs) and TRPV1 receptors also contribute to tissue acidification sensing. ASICs, NHEs, and TRPV1 receptors are found to be expressed in nociceptive nerve fibers. ASIC inhibitors reduce peripheral acidinduced hyperalgesia and suppress inflammatory pain. Also, it was shown that pharmacological inhibition of NHE1 promotes nociceptive behavior in acute pain models, whereas inhibition of TRPV1 receptors gives relief.The murine skin-nerve preparation was used in this study to assess the activation of native polymodal nociceptors by mild acidification (pH 6.1). We have found that diminazene, a well-known antagonist of ASICs did not suppress pH-induced activation of CMH-fibers at concentrations as high as 25 μM. Moreover, at 100 μM, it induces the potentiation of the fibers' response to acidic pH. At the same time, this concentration virtually completely inhibited ASIC currents in mouse DRG neurons (ІС50=17.0 ± 4.5 μМ). Non-selective ASICs and NHEs inhibitor EIPA (5-(N-ethyl-N-isopropyl)amiloride) at 10 μM, as well as selective NHE1 inhibitor zoniporide at 0.5 μM induced qualitatively the same effects as 100 µM of diminazene.Our results indicate that proton-induced excitation of afferent nerve terminals induced by mild acidification occurs mainly due to the NHE1, rather than acid-sensing ion channels. At high concentrations, diminazene acts as a weak blocker of the NHE. It lacks chemical similarity with amiloride, EIPA, and zoniporide, so it may represent a novel structural motif for the development of NHE antagonists. However, the effect of diminazene on the acid-induced excitation of primary nociceptors remains enigmatic and requires additional investigations.